Saving cognitive outcome data in Alzheimer's disease clinical trials during the COVID‐19 pandemic: Commentary on the virtual administration of the ADAS‐Cog - Schwab, Nadine A. (Alzheimers Dement (N Y), 2020)
Elderly participants in Alzheimer's disease (AD) clinical trials are at high risk of morbidity and mortality with interpersonal exposure to COVID‐19, a situation that is likely to continue for the foreseeable future. Yet, in‐person neuropsychological assessments remain the mainstay primary outcomes for clinical trials seeking prevention and cure for AD. The Alzheimer's Disease Assessment Scale‐Cognitive (ADAS‐Cog) is among the most commonly used cognitive assessment in AD clinical trials, and though currently lacking specific guidelines for virtual administrations, it can be used remotely with appropriate modifications and considerations. Here we propose a novel method of virtual administration of the ADAS‐Cog, which considers workarounds for technological and human limitations imposed when the participant is no longer sitting across from the test administrator.